(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article discusses issues related to the interpretation of the concept of "selfishness" and the issues raised by Leo Tolstoy in this area. The issues of the formation of the worldview of the famous writer are considered, as well as the evolution of the worldview of the great writer in this matter, which eventually led Tolstoy to create images reflecting a certain philosophical position of the author himself.